2011
DOI: 10.1016/j.jtcvs.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of pulmonary artery rehabilitation in patients with pulmonary atresia, ventricular septal defect, pulmonary artery hypoplasia, and major aortopulmonary collaterals

Abstract: Pulmonary artery rehabilitation allows complete repair in the majority of patients with pulmonary atresia, ventricular septal defect, hypoplastic pulmonary arteries, and major aortopulmonary collaterals. However, long-term management often requires pursuit of the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…As Dragulescu stated in 2011, rehabilitation of the PAs with RV‐PA connection is successful, allowing complete surgical repair with good survival and functional status in the majority of the cases. Rumball et al found that the Norwood procedure with RV–PA conduit is associated with better distributed central pulmonary artery growth than the SPS.…”
Section: Discussionmentioning
confidence: 98%
“…As Dragulescu stated in 2011, rehabilitation of the PAs with RV‐PA connection is successful, allowing complete surgical repair with good survival and functional status in the majority of the cases. Rumball et al found that the Norwood procedure with RV–PA conduit is associated with better distributed central pulmonary artery growth than the SPS.…”
Section: Discussionmentioning
confidence: 98%
“…Surgical management of PA with MAPCAs has improved the prognosis for this complex heart disease, but the timing and surgical options are still in evolution. Optimal timing for surgical intervention for PA/VSD/MAPCA should be between three and six months [10,11] . In some circumstances, however, intervention cannot postpone until the ideal three to six months period.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Stanford group [10] proposed a new algorithmic approach to the diagnostic workup and treatment of PA/VSD/MAPCAs in 2009. They emphasized that catheterization should be a part of surgical planning and carried out at the initial diagnosis time.…”
Section: Discussionmentioning
confidence: 99%
“…A single ventricle is formed as a rare pathology and with the possibility of surgical treatment by means of palliative surgeries, when it is diagnosed in [6,7] the age and weight of the patient are determinants for their survival, as well as the early diagnosis of the anomaly, in order to avoid complications such as pulmonary hypertension, heart failure and death. that the patient can perform the surgery at an appropriate age, without it worsening his physical condition, for which he is supported with medication and continuous medical care [8][9][10]. In this patient, the symptoms that I present during the first hours of life such as cyanosis and difficulty feeding and the presence of heart murmur made suspicion In the case of complex heart disease, the hospital where this case was analyzed has no hemodynamic or cardiac surgery service, so it had to move urgently with life support and drugs to a third level for its specialized care.…”
Section: Discussionmentioning
confidence: 99%